Silane-Based Hybrid Coatings for the Corrosion Protection of AA 2024-T3 Alloy - Brenda Diane Pereira Martins; Laís de Campos Barbieri; Amanda Alvarenga Coutinho Silva; Naiana Serafim Goulart; Renata Batista Rivero Garcia; Luciana de Simone Cividanes; Elizabete Yoshie Kawachi (Journal of Aerospace Technology and Management, 2020)
In order to contribute to the corrosion protection of aluminum alloys, silane-based hybrid coatings have been widely studied in the aerospace industry for their good adhesion to aluminum substrates, compatibility with organic paintings and to protect the underlying material, in addition to being much less toxic than the commonly used chromatization process. In this work, hybrid and inorganic sol-gel coatings were evaluated as corrosion inhibitor films for AA2024-T3 alloy. The films were characterized by linear polarization resistance (LPR) and scanning electron microscopy (SEM), which indicated that these coatings provide a lower tendency for the substrate corrosion.